Aging and Inhibition of Return to Locations and Objects - Huether, Asenath X. A.; Langley, Linda K.; Thomas, Laura E. (Frontiers in Psychology, 2021)
Inhibition of return (IOR) is thought to reflect a cognitive mechanism that biases attention from returning to previously engaged items. While models of cognitive aging have proposed deficits within select inhibitory domains, older adults have demonstrated preserved IOR functioning in previous studies. The present study investigated whether inhibition associated with objects shows the same age patterns as inhibition associated with locations. Young adults (18-22 years) and older adults (60-86 years) were tested in two experiments measuring location- and object-based IOR. Using a dynamic paradigm (Experiment 1), both age groups produced significant location-based IOR, but only young adults produced significant object-based IOR, consistent with previous findings. However, with a static paradigm (Experiment 2), young adults and older adults produced both location- and object-based IOR, indicating that object-based IOR is preserved in older adults under some conditions. The findings provide partial support for unique age-related inhibitory patterns associated with attention to objects and locations.